Elaboración de chocolate artesanal con saborizantes naturales en el cantón Shushufindi provincia de Sucumbíos. - Chanaluisa Oña, Jefferson Romario (2021)
In the Shushufindi canton located in the Sucumbíos province in Ecuador, cultivate 8313 hectares of cocoa with export quality per year. However, there is a waste of 1,072 hectares of cocoa because the large chocolate companies in the country only assimilate 87.1% of the total cocoa production in the territory, generating economic losses in the producers. An alternative to taking advantage of the excellent raw material is to create small companies dedicated to the local production of chocolate. The general aim of the work is the elaboration of artisan chocolate combining the cocoa extract with different natural flavors, thus getting a quality product that meets the standards established in the INEN norms of Ecuador and the international CODEX Alimentary for the production of chocolate and its derivatives. The research is descriptive, explanatory, and experimental. The methods used were analysis and synthesis and hypothetical deductive. The causes that have generated the waste of raw material were studied, such as overproduction and the preference of cocoa from coastal areas over that produced in the sector, because of the cost of transportation. The physical and chemical properties of cocoa were analyzed, combining fruits and cocoa, which allowed us to propose a production model for artisan chocolate. For the validation of the work, techniques such as the survey were used that allowed to know the results of the fruits preferred by the population to combine them with the cocoa paste, and thus get consumer acceptance for the product. The results got to show that pineapple, strawberry, and borojó are the best option to mix with cocoa paste. The work concluded that the elaboration of artisan chocolate with fruit filling has a good reception among the residents of the town.